Does performance pay increase the risk of marital instability? - Mehrzad B. Baktash; John S. Heywood; Uwe Jirjahn (Universität Trier, Fachbereich IV - Volkswirtschaftslehre, 2023)
This paper uses German survey data on married couples to examine the association of performance pay at work and subsequent separation or divorce. Despite extensive controls, performance pay remains associated with an increased probability of separation or divorce. Yet, the results are entirely gender specific. When husbands earn performance pay, no association with marital instability is found. When wives earn performance pay, the association is large and robust. This pattern persists across a variety of modeling choices and attempts to account for endogeneity. We argue that the pattern fits theoretical expectations and discuss the implications.
Keywords: J33; I31; J32; 330; Performance Pay; Separation; Divorce; Gender